The perfect witness - Siegel, Barry (Ballantine Books, 1999)
They used to be partners -- Greg Monarch and Ira Sullivan, a couple of do-good lawyers in central California. But it all went bad for Ira. Bad enough that he wakes up in jail one day staring at a death sentence for murder. Only Greg Monarch has a prayer of getting him off -- if he's willing to cross certain ethical lines.